2013
DOI: 10.3390/ijms14035978
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Multiple Signaling Pathways Determines Differences in the Osteogenic Potential and Tissue Regeneration of Neural Crest-Derived and Mesoderm-Derived Calvarial Bones

Abstract: The mammalian skull vault, a product of a unique and tightly regulated evolutionary process, in which components of disparate embryonic origin are integrated, is an elegant model with which to study osteoblast biology. Our laboratory has demonstrated that this distinct embryonic origin of frontal and parietal bones confer differences in embryonic and postnatal osteogenic potential and skeletal regenerative capacity, with frontal neural crest derived osteoblasts benefitting from greater osteogenic potential. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 128 publications
2
29
0
Order By: Relevance
“…Both CNCC derived and paraxial mesoderm derived osteoprogenitor cells undergo intramembranous ossification to generate corresponding skull elements; however, they show some differences in osteogenic potential and skeletal regenerative capacity [26]. Osteoblasts from neural crest-derived bones such as the frontal bone feature a higher level of activation of FGF signaling pathways compared with osteoblasts from paraxial mesoderm-derived bones such as parietal bones [27, 28].…”
Section: Skull Osteogenesis and Cranial Suturesmentioning
confidence: 99%
“…Both CNCC derived and paraxial mesoderm derived osteoprogenitor cells undergo intramembranous ossification to generate corresponding skull elements; however, they show some differences in osteogenic potential and skeletal regenerative capacity [26]. Osteoblasts from neural crest-derived bones such as the frontal bone feature a higher level of activation of FGF signaling pathways compared with osteoblasts from paraxial mesoderm-derived bones such as parietal bones [27, 28].…”
Section: Skull Osteogenesis and Cranial Suturesmentioning
confidence: 99%
“…8,9 We have previously showed that the disparate embryonic tissue origin of mammalian calvarium 10 leads to significant differences in the activity of key signaling pathways that govern osteogenic and regenerative potential. [11][12][13][14][15] Recently, we have identified that enhanced transforming growth factor beta (TGFb) signaling in mesoderm-derived parietal bone osteoblasts (PObs) has a key role in determining their elevated apoptotic activity and diminished osteogenic capacity. 16 This finding provides the impetus for our current study, which investigates the possibility of potentiating bone regeneration in the mammalian calvarium through inhibition of TGFb signaling by employing the small molecule SB431542.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced activation of Wnt signaling is capable to transform the physiological behavior of parietal bone into a degree similar to neural crest derived frontal bone [6]. Besides, frontal bone tissues show low apoptosis when stimulated by TGF signaling [7]. Due to superior activities of osteoblasts and bone regeneration within frontal bone, a novel thought for craniofacial construction–endogenous calvarial regeneration has been proposed.…”
Section: Introductionmentioning
confidence: 99%